Comparison between Grating Imaging and Transient Grating Techniques on Measuring Carrier Diffusion in Semiconductor. Issue 4 (2nd October 2018) - Chen, Ke; Meng, Xianghai; He, Feng; Zhou, Yongjian; Jeong, Jihoon; Sheehan, Nathanial; Bank, Seth R; Wang, Yaguo
ABSTRACT: Optical grating technique, where optical gratings are generated via light inference, has been widely used to measure charge carrier and phonon transport in semiconductors. In this paper, compared are three types of transient optical grating techniques: transient grating diffraction, transient grating heterodyne, and grating imaging, by utilizing them to measure carrier diffusion coefficient in a GaAs/AlAs superlattice. Theoretical models are constructed for each technique to extract the carrier diffusion coefficient, and the results from all three techniques are consistent. Our main findings are: (1) the transient transmission change ∆ T / T 0 obtained from transient grating heterodyne and grating imaging techniques are identical, even these two techniques originate from different detection principles; and (2) by adopting detection of transmission change (heterodyne amplification) instead of pure diffraction, the grating imaging technique (transient grating heterodyne) has overwhelming advantage in signal intensity than the transient grating diffraction, with a signal intensity ratio of 315:1 (157:1).